(untitled) (Khairulummah, 2023)
Arabic language has a special and distinctive place in the hearts of Muslims, and it has a close relation with Islamic religion. And this study named accusative noun by removing genitive to an object in the holy Quran, discussed an important matter from grammatical issues and the main purpose of this study is to apply Arabic rules of structures that are being covered by the accusative noun. It happened many times in an accusative object, and scholars and interpreters discussed about that.